Sistem Minimum Berbasis Mikrokontroler ATmega2560 sebagai Sistem Pengaman pada Analogi Lemari Penyimpanan Brankas - Muchammad Takdir Sholehati; Arief Goeritno (Universitas Syiah Kuala, 2018)
A minimum system based on ATmega2560 microcontroller has been created that functioned as a safety system in the analogy of the cupboard for storage of the safes. Making the minimum system is done through a number of phases, namely integrating the system, programming against the microcontroller system, and validation test in the form of system performance measurement through giving the forced state. System integration is in the form of installing a device on two lines in the input port and two lines in the output port of the microcontroller. Programming is based on algorithms and the syntax of Arduino IDE-based through 6 (six) stages, namely pins configuration, variable and constants declaration, initialization, main program, retrieved and send data, and output. The validation test is carried out in the form of 4 (four) conditions, namely a) when the RFID module is not detected, b) when the card is detected by the RFID module, c) when the door is opened, and the buzzer is